Copper, Zinc, Nickel and Chromium Uptake by "Kangkong Air" (Ipomea aquatica Forsk). - Low, K. S.; Lee, C. K. (1981)
The uptake of copper, zinc, nickel and chromium from nutrient solutions enriched with these metals using "Kangkong air" (Ipomea aquatica Forsk) was studied. This aquatic plant demonstrated the ability to remove copper and nickel rapidly and to remove zinc and chromium less rapidly by root absorption and concentration. "Kangkong air" showed the ability to absorb up to 0.552 mg of copper, 0.213 mg of nickel, 0.090 mg of chromium and 0.009 mg of zinc per gram dry plant material when exposed for a 48 hour period to nutrient solutions containing 5.00 ppm of their metals. A study of the uptake of copper, nickel and chromium by "Kangkong air" and water hyacinths (Eichhorria crassipes) (Mart.) Solms in wastewater from an electroplating plant is also discussed.